HUMAN CAPITAL OF CHAR PEOPLE’S LIVELIHOODS IN BANGLADESH - NOMAN, ABU SALEH MOHAMMAD (CenRaPS Journal of Social Sciences, 2020)
Sustainable livelihoods are achieved through access to a range of livelihoods capitals which are combined in the pursuit of different livelihood strategies. Human capital represents the skills, knowledge, education, ability to labor and good health that together enable people to pursue their livelihood strategies. It is therefore necessary, though not on its own sufficient, for the achievement of positive livelihoods outcomes. The study examines the sustainability of human assets of livelihoods of char people and explores the influence of land and river, and the impact of climate change on their natural assets. The study found that the livelihood pattern of the people of char is insecure, vulnerable and unsustainable. They are deprived of education-both modern and traditional and health services or medical facilities. There is a strong relationship ship among education, gender and patriarchy. It is recommended that, there is a strong need for institutional support to assist them in developing their human capital.